A Multi Depot Multi Product Split Delivery Vehicle Routing Problem with Time Windows: A Real Cash in Transit Problem Application in Istanbul, Turkey - Ertuğrul Ayyıldız; Mehmet Can Şahin; Alev Taşkın (Journal of Transportation and Logistics)
In today’s highly competitive world market, companies and private enterprises deliver their business on time. Their value and total costs play an essential role in their positions in the market. The most costly and difficult factors to regulate are shipping and distribution systems. The high cost of transportation and distribution systems is one reason for the increase in vehicle routing problems and studies in logistics network design. Vehicle routing problems (VRPs) are concerned with finding the optimal or near-optimal routes for vehicles to follow in meeting the demands of customers or facilities. The cash in transit (CIT) problem as a version of the VRP, deals with the planning of money distribution from the depot(s) to Automated Teller Machines (ATMs) safely and quickly. This paper investigates a novel CIT problem, which is a variant of split delivery VRP with time windows. To establish a novel approach to the CIT problem, different money currencies are considered. Also, multiple depots and heterogeneous fleet are included in the problem. To handle the CIT problem more realistically, a risk constrained multi-depot multi-product heterogeneous fleet split delivery VRP with a time windows formulation is proposed. The problem is hence formulated as a mixed-integer mathematical model. The mathematical model is run for different scenarios and optimal routes are obtained. The experimental analysis shows that the mathematical model developed, can help decision-makers to obtain effective solutions for their CIT operations with different money currencies.